Penegakan Hak-Hak Alam Di Indonesia Ditinjau Dalam Perspektif Deep Ecology Dan Should Trees Have Standing? - Juniarto Prakoso; Agustinus Supriyanto (El-Dusturie, 2026)
Abstract: Environmental protection in Indonesia still relies on an anthropocentric paradigm that positions nature as an object of exploitation, not as an entity with a right to exist. This condition is reflected in various legal instruments, ranging from the 1945 Constitution of the Republic of Indonesia, Law No. 32 of 2009 concerning Environmental Governance, Law No. 41 of 1999 concerning Forestry, to Law No. 6 of 2023 concerning Job Creation, as well as in judicial practices that consistently require direct harm to humans as the basis for a lawsuit. This study aims to analyze the state of enforcement of natural rights in Indonesia and formulate a model for its enforcement through the perspective of "Deep Ecology" by Arne Naess and the concept of "Should Trees Have Standing?" by Christopher D. Stone. This study uses a normative juridical method with legislative, conceptual, and comparative approaches to countries that have recognized the rights of nature, such as Ecuador, Bolivia, New Zealand, India, and Colombia. Research findings indicate that regulations and judicial practices in Indonesia have not yet recognized nature as a legal subject, resulting in reactive, rather than preventive, environmental protection. This study identifies four potential actors as guardians of nature: Indigenous Peoples, the Ministry of Environment and Forestry, Environmental Non-Governmental Organizations, and the proposed Environmental Ombudsman. Each of these actors has limitations, leading to the formulation of a multi-level and collaborative guardian model as an implementation mechanism. This study recommends environmental law reform through recognizing the legal standing of nature, strengthening independent guardian institutions, and redirecting the AMDAL system and ecological restorative justice to achieve ecologically just environmental law enforcement in Indonesia.   Keywords: Rights of Nature; Deep Ecology; Should Trees Have Standing?; Environmental Law Enforcement; Ecological Justice.   Abstrak: Perlindungan lingkungan hidup di Indonesia masih bertumpu pada paradigma antroposentris yang memposisikan alam sebagai objek pemanfaatan, bukan sebagai entitas yang memiliki hak untuk eksis. Kondisi ini tercermin dalam berbagai instrumen hukum, mulai dari UUD NRI 1945, UU No. 32 Tahun 2009 tentang PPLH, UU No. 41 Tahun 1999 tentang Kehutanan, hingga UU No. 6 Tahun 2023 tentang Cipta Kerja, serta dalam praktik peradilan yang senantiasa mensyaratkan kerugian langsung pada manusia sebagai dasar gugatan. Penelitian ini bertujuan menganalisis kondisi penegakan hak-hak alam di Indonesia dan merumuskan model penegakannya melalui perspektif “Deep Ecology” dari Arne Naess dan gagasan “Should Trees Have Standing?” dari Christopher D. Stone. Penelitian menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif terhadap negara-negara yang telah mengakui hak alam, seperti Ekuador, Bolivia, Selandia Baru, India, dan Kolombia. Hasil penelitian menunjukkan bahwa regulasi dan praktik peradilan di Indonesia belum mengakui alam sebagai subjek hukum sehingga perlindungan lingkungan bersifat reaktif, bukan preventif. Penelitian ini mengidentifikasi empat aktor potensial sebagai guardian alam, yakni Masyarakat Hukum Adat, Kementerian Lingkungan Hidup dan Kehutanan, Lembaga Swadaya Masyarakat Lingkungan, dan Ombudsman Lingkungan Hidup yang diusulkan, yang masing-masing memiliki keterbatasan, sehingga dirumuskan model guardian berjenjang dan kolaboratif sebagai mekanisme implementasi. Penelitian ini merekomendasikan reformasi hukum lingkungan melalui pengakuan legal standing bagi alam, penguatan kelembagaan guardian independen, serta reorientasi sistem AMDAL dan keadilan restoratif ekologis guna mewujudkan penegakan hukum lingkungan yang berkeadilan ekologis di Indonesia. Kata Kunci: Hak-hak alam; Deep Ecology; Should Trees Have Standing?; Penegakan Hukum Lingkungan; Keadilan Ekologis.